Serious adverse events and visual outcomes of rescue therapy using adjunct bevacizumab to laser and surgery for retinopathy of prematurity. The Indian Twin Cities Retinopathy of Prematurity Screening database Report number 5. Issue 4 (25th December 2012) - Jalali, Subhadra; Balakrishnan, Divya; Zeynalova, Zarifa; Padhi, Tapas Ranjan; Rani, Padmaja Kumari
Abstract : Aim: To report serious adverse events and long-term outcomes of initial experience with intraocular bevacizumab in retinopathy of prematurity (ROP). Methods: Consecutive vascularly active ROP cases treated with bevacizumab, in addition to laser and surgery, were analysed retrospectively from a prospective computerised ROP database. Primary efficacy outcome was regression of new vessels. Secondary outcomes included the anatomic and visual status. Serious systemic and ocular adverse events were documented. Results: 24 ROP eyes in 13 babies, received single intraocular bevacizumab for severe stage 3 plus after failed laser (seven eyes), stage 4A plus (eight eyes), and stage 4B/5 plus (nine eyes). Drug was injected intravitreally in 23 eyes and intracamerally in one eye. New vessels regressed in all eyes. Vision salvage in 14 of 24 eyes and no serious neurodevelopmental abnormalities were noted up to 60 months (mean 30.7 months) follow-up. Complications included macular hole and retinal breaks causing rhegmatogenous retinal detachment (one eye); bilateral, progressive vascular attenuation, perivascular exudation and optic atrophy in one baby, and progression of detachment bilaterally to stage 5 in one baby with missed follow-up. One baby who received intracameral injection developed hepatic dysfunction. One eye of this baby also showed a large choroidal rupture. Conclusions: Though intraocular bevacizumab, along with laser and surgery salvaged vision in many otherwise progressive cases of ROP, vigilance and reporting of serious adverse events is essential for future rationalised use of the drug. We report one systemic and four ocular adverse events that require consideration in future use of the drug.